Hypoxia-induced lipid peroxidation in the brain during postnatal ontogenesis - Rauchová, Hana; Vokurková, Martina; Koudelová, Jitka (Physiological research, 2012)
Reactive oxygen species (ROS) are common products of the physiological metabolic reactions, which are associated with cell signaling and with the pathogenesis of various nervous disorders. The brain tissue has the high rate of oxidative metabolic activity, high concentration of polyunsaturated fatty acids in membrane lipids, presence of iron ions and low capacity of antioxidant enzymes, which makes the brain very susceptible to ROS action and lipid peroxidation formation. Membranes of brain cortex show a higher production of thiobarbituric acid-reactive substances (TBARS) in prooxidant system (ADP.Fe(3+)/NADPH) than membranes from the heart or kidney. Lipid peroxidation influences numerous cellular functions through membrane-bound receptors or enzymes. The rate of brain cortex Na(+),K(+)-ATPase inhibition correlates well with the increase of TBARS or conjugated dienes and with changes of membrane fluidity. The experimental model of short-term hypoxia (simulating an altitude of 9000 m for 30 min) shows remarkable increase in TBARS in four different parts of the rat brain (cortex, subcortical structures, cerebellum and medulla oblongata) during the postnatal development of Wistar rat of both sexes. Young rats and males are more sensitive to oxygen changes than adult rats and females, respectively. Under normoxia or hypobaric hypoxia both ontogenetic aspects and sex differences play a major role in establishing the activity of erythrocyte catalase, which is an important part of the antioxidant defense of the organism. Rats pretreated with L-carnitine (and its derivatives) have lower TBARS levels after the exposure to hypobaric hypoxia. The protective effect of L-carnitine is comparable with the effect of tocopherol, well-known reactive species scavenger. Moreover, the plasma lactate increases after a short-term hypobaric hypoxia and decreases in L-carnitine pretreated rats. Acute hypobaric hypoxia and/or L-carnitine-pretreatment modify serum but not brain lactate dehydrogenase activity. The obtained data seem to be important because the variations in oxygen tension represent specific signals of regulating the activity of many specific systems in the organism.
Keywords: Animals; krysa rodu Rattus; peroxidace lipidů; ženské pohlaví; mužské pohlaví; pohlavní dimorfismus; látky reagující s kyselinou thiobarbiturovou; Reactive Oxygen Species; Hypoxia; stárnutí; Rats; Male; Thiobarbituric Acid Reactive Substances; hypoxie; Carnitine; zvířata; potkani Wistar; Sex Characteristics; reaktivní formy kyslíku; karnitin; Lipid Peroxidation; Rats, Wistar; Aging; Female